2021
DOI: 10.1177/00220221211025100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Societal Culture on Covid-19 Morbidity and Mortality across Countries

Abstract: Researchers have begun exploring the impact of societal culture on Covid-19 outcomes (morbidity and mortality). However, emerging findings need integration with prior literature on societal culture and infectious diseases. Moreover, accumulation of knowledge warrants an update while overcoming certain limitations of samples as well as construct validity concerns. Accordingly, hypotheses are derived based on extant evidence proposing the impact of certain cultural practices on Covid-19 outcomes across countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
(178 reference statements)
0
16
1
Order By: Relevance
“…However, this research differs from others; for example, Huynh (2020) [69] found that a country with a higher uncertainty avoidance index from the Hofstede (2001) dimension made people strictly follow the rules by avoiding gathering in public areas or strictly complying with swift quarantine measures and effective containment of COVID-19 cases (Kumar, 2021) [70]. Countries with high levels of uncertainty avoidance have the ability to control the spread of the epidemic better than a country with low levels of uncertainty avoidance because people have more "tolerance" (Mattaa et al, 2021) [71].…”
Section: -Discussioncontrasting
confidence: 68%
“…However, this research differs from others; for example, Huynh (2020) [69] found that a country with a higher uncertainty avoidance index from the Hofstede (2001) dimension made people strictly follow the rules by avoiding gathering in public areas or strictly complying with swift quarantine measures and effective containment of COVID-19 cases (Kumar, 2021) [70]. Countries with high levels of uncertainty avoidance have the ability to control the spread of the epidemic better than a country with low levels of uncertainty avoidance because people have more "tolerance" (Mattaa et al, 2021) [71].…”
Section: -Discussioncontrasting
confidence: 68%
“…Different countries have reacted and responded to the ongoing COVID-19 situation differently ( Babu et al, 2021 , Ihekweazu and Agogo, 2020 , Oh et al, 2020 ). This has attracted researchers to explore the impact of culture on COVID-19 growth ( Gokmen et al, 2021 , Kumar, 2021 , Ibanez and Gyanendra Singh, 2020 ). The researches have established significant direct impact of cultural factors on COVID-19 growth.…”
Section: Discussionmentioning
confidence: 99%
“…Third, surprisingly few studies explicitly focused on culture and measured cultural dimensions. We have to consider that we only included research referring to the early phase of the pandemic and it seems likely that such culture‐focused research might be more feasible in later than in very early phases of such a pandemic (e.g., as it relies on international data on the pandemic itself, involving a larger number of countries and thus from later stages of the pandemic, e.g., Gelfand et al, 2021; Kumar, 2021). This signals a potential issue related to a time lag between the outbreak of major global health crises (and the need for immediate international research evidence) and first empirical cross‐cultural research evidence addressing the role of culture in this early phase.…”
Section: Discussionmentioning
confidence: 99%